C-Terminal-Deleted Prion Protein Fragment Is a Major Accumulated Component of Systemic PrP Deposits in Hereditary Prion Disease With a 2-Bp (CT) Deletion in PRNP Codon 178. Issue 11 (November 2016) - Honda, Hiroyuki; Matsuzono, Kosuke; Fushimi, Soichiro; Sato, Kota; Suzuki, Satoshi O.; Abe, Koji; Iwaki, Toru
Abstract : Prion protein (PrP) has 2 glycosylated sites and a glycosylphosphatidylinositol (GPI) anchor on the C-terminal. Reports on genetic prion disease with GPI anchorless PrP are very limited. In this study, we characterized the molecular alterations of mutated PrP in a 37-year-old female autopsy case with a recently identified PRNP mutation involving a 2-bp deletion in codon 178 that results in a premature stop codon mutation in codon 203. Postmortem examination revealed numerous irregularly shaped coarse PrP deposits and multicentric plaques in the brain that were mainly comprised of C-terminal deleted abnormal PrP primarily derived from the mutant allele. Additionally, abnormal PrP deposits were detected in almost all other examined organs. PrP was mainly deposited in peripheral nerves, smooth muscles, and blood vessels in non-CNS tissues. Western blot analysis after proteinase K treatment showed protease-resistant PrP (PrP res ) signals with a molecular weight of 9 kDa; weak PrP res smear signals of 9 to ∼80 kDa were also noted. Gel filtration revealed that PrP res oligomers were mainly composed of the PrP fragments. In conclusion, the mutated PrP lacking that GPI anchor was truncated shortly and deposited in almost every examined organ.